MicroRNA-21-3p Engineered Umbilical Cord Stem Cell-Derived Exosomes Inhibit Tendon Adhesion - Yao Z; Li J; Wang X; Peng S; Ning J; Qian Y; Fan C (Dove Medical Press, 2020)
Zhixiao Yao,1,* Juehong Li,1,* Xu Wang,1 Shiqiao Peng,2 Jiexin Ning,3 Yun Qian,1 Cunyi Fan1 1Department of Orthopaedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of China; 2Department of Endocrinology, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of China; 3Department of Plastics, Binzhou People’s Hospital, Binzhou 256610, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun Qian; Cunyi FanDepartment of Orthopaedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of ChinaTel +86 21-64369181Email lollipopcloudland@foxmail.com; cyfan@sjtu.edu.cnPurpose: As a common complication of tendon injury, tendon adhesion is an unresolved problem in clinical work. The aim of this study was to investigate whether human umbilical cord mesenchymal stem cell-derived exosomes (HUMSC-Exos), one of the most promising new-generation cell-free therapeutic agents, can improve tendon adhesion and explore potential-related mechanisms.Methods: The rat Achilles tendon injury adhesion model was constructed in vivo, and the localization of HUMSC-Exos was used to evaluate the tendon adhesion. Rat fibroblast cell lines were treated with transforming growth factor β 1 (TGF-β 1) and/or HUMSC-Exos in vitro, and cell proliferation, apoptosis and gene expression were measured. MicroRNA (miRNA) sequencing and quantitative PCR (qPCR) analysis confirmed differential miRNAs. A specific miRNA antagonist (antagomir-21a-5p) was used to transform HUMSC-Exos and obtain modified exosomes to verify its efficacy and related mechanism of action.Results: In this study, we found HUMSC-Exos reduced rat fibroblast proliferation and inhibited the expression of fibrosis genes: collagen III (COL III) and α-smooth muscle actin (α-SMA) in vitro. In the rat tendon adhesion model, topical application of HUMSC-Exos contributed to relief of tendon adhesion. Specifically, the fibrosis and inflammation-related genes were simultaneously inhibited by HUMSC-Exos. Further, miRNA sequencing of HUMSCs and HUMSC-Exos showed that miR-21a-3p was expressed at low abundance in HUMSC-Exos. The antagonist targeting miR-21a-3p was recruited for treatment of HUMSCs, and harvested HUMSC-Exos, which expressed low levels of miR-21a-3p, and expanded the inhibition of tendon adhesion in subsequent in vitro experiments.Conclusion: Our results indicate that HUMSC-Exos may manipulate p65 activity by delivering low-abundance miR-21a-3p, ultimately inhibiting tendon adhesion. The findings may be promising for dealing with tendon adhesion.Keywords: HUMSC, exosome, tendon adhesion, TGF-β 1, p65, miR-21a-3p, NF-κB